Selected Methods of Therapeutic Interactions With People With Mild Symptoms of Autism Spectrum Disorder - Marta, Kopańska; Justyna, Chojdak-Łukasiewicz; Marta, Sochocka; Jerzy, Leszek; Justyna, Podgórska-Bednarz; Agnieszka, Banaś-Ząbczyk̨; Danuta, Ochojska (Frontiers in Psychiatry, 2022)
The authors present the behavioral aspects of interaction in people with autism spectrum dis-orders (ASD), taking into account some aspects of pharmacotherapy. The individual approach, with respect to emotional, social and cognitive functioning, is very important in the therapy of people with ASD. The specificity of symptoms and their severity in people with ASD results from deficits/disfunction of various areas of the brain and are associated with different levels of in-telligence. The subject of considerations in this manuscript are selected methods of interac-tions with ASD patients with IQ within the normal range. Due to their different ways of functioning, these people often find it difficult to adapt to social expectations. The most important thing is to understand their way of perceiving themselves and the surrounding world, in order to support them in coping with everyday challenges. The effectiveness of therapy depends to a large extent on cooperation between educational institutions. It is also necessary to stay in touch with specialized clinics, including a mental health counselling centre. However, in the case of children and adolescents, the basis is the therapist’s cooperation with parents. Also concerning adults with ASD, systemic family therapy is important.